(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
University of Milan began researches at Nora (Sardinia) in 2002, directed by Professor G. Bejor, in the heart of the Roman city: the central insula, between the theatre and the so-called Temple of Eshmun, occupied by the grand Central Baths and several domus with standing remains. The recent excavations have recognized the complex stratigraphy of this area from the early imperial period until the 7th century A.D., showing the continuity of the city’s occupation from the Phoenician period until the threshold of the late antiquity.